Free-volume dependent atomic dynamics in beta relaxation pronounced La-based metallic glasses. (15th October 2015) - Wang, X.D.; Ruta, B.; Xiong, L.H.; Zhang, D.W.; Chushkin, Y.; Sheng, H.W.; Lou, H.B.; Cao, Q.P.; Jiang, J.Z.
Graphical abstract: Abstract: The atomic dynamics and its structure dependence in a glass are fundamental issues but still little understood for decades. Through state-of-the-art experiment and simulation, we reveal that the annihilation of excess free volume in a β-relaxation pronounced La–Al–Ni metallic glass slows down the atomic motion by one order of magnitude upon annealing, which is mainly caused by the change of subatomic cavities and enhanced network structure resulting from the presence of Ni atoms, showing significant difference from a β-relaxation unpronounced La–Al–Cu glass. Our findings provide insights into the dynamics and atomic structure of La-based metallic glasses and will be helpful in understanding the microscopic dynamic behavior of metallic glasses in general.